PENINGKATAN POTENSI DESA MELALUI UMKM BERBASIS DIGITALISASI DAN INOVASI PRODUK DI DESA WONOSARI - rahayu, eka; As’at, Abu Rizal; Saputra, Adam Ridho; Na’imah, Afifatul; Fauziah, Ahmirurotul; Khasanah, Alfi; Azizah, Alfi Nur; Madinah, Dina Maratul; Rohida, Erin Nur; Nasikin, Fahri; Fergiawan, Fatah; Aziz, Jhovendy Mohamad; Huda, Muhammad Nur; Khomairoh, Nabilatul; Brenanda, Ocha Adelia; Sari, Putri Herdiana; Chofshoh, Umi (Abdimas IAI Ngawi, 2024)
The lack of knowledge of  Micro, Small and Medium Enterprises (MSME) actors regarding the importance of using digital technology in the current digitalization era results in products not being widely known by the market. The number of competitors also affects customer and consumer loyalty. MSME actors must produce new innovations and breakthroughs to be able to survive in the midst of a dynamic market. This study aims to educate the people of Wonosari Village regarding the use of digital media in expanding the market and the importance of product innovation. The method used is the Participatory Action Research (PAR) method. The final result of this activity is a renewal of insight for MSME actors and the people of Wonosari Village regarding the use of Google Maps as a digital platform used for market expansion and innovation of flavor variants for MSME products Kurnia Keripik in the form of chocolate banana chips. Keywords: MSME, Digital, Innovation Abstrak: Minimnya pengetahuan pelaku Usaha Mikro Kecil Menengah (UMKM) terhadap pentingnya penggunaan teknologi digital di era digitalisasi saat ini mengakibatkan produk tidak dikenal luas oleh pasar. Banyaknya kompetitor juga mempengaruhi loyalitas pelanggan dan konsumen. Pelaku UMKM harus melahirkan inovasi dan terobosan baru untuk dapat bertahan ditengah-tengah pasar yang dinamis. Pengabdian ini bertujuan untuk mengedukasi masyarakat Desa Wonosari terkait pemanfaatan media digital dalam perluasan pasar dan pentingnya inovasi sebuah produk. Metode yang digunakan, yaitu metode Participatory Action Research (PAR). Hasil akhir dari kegiatan ini adalah pembaharuan wawasan bagi pelaku UMKM dan masyarakat Desa Wonosari berkaitan dengan penggunaan google maps sebagai platform digital yang digunakan untuk perluasan pasar dan inovasi varian rasa untuk produk UMKM Kurnia Keripik berupa keripik pisang coklat. Kata Kunci: UMKM, Digital, Inovasi